Confronting Emergent Nuclear-Armed Regional Adversaries Prospects for Neutralization, Strategies for Escalation Management - Morgan, Forrest E. (RAND Corporation, 2015)
This report discusses the challenges associated with potential confrontations between the United States and hostile states with small nuclear arsenals. It examines prospects for neutralizing their nuclear capabilities via combinations of offensive and defensive options at varying levels of opponent nuclear development and managing escalation risks in conventional wars with them across a range of scenarios.